2022
DOI: 10.5114/pm.2022.127038
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological therapy options for chemotherapy-related cognitive impairment

Abstract: Chemioterapia daje pacjentom z nowotworami szansę na wyleczenie oraz wydłużenie życia, może jednak powodować także wiele skutków ubocznych. Jednym z nich są zaburzenia funkcji kognitywnych nazywane chemobrain. Chemobrain charakteryzuje się deficytami w wielu obszarach poznawczych, w tym pamięci, uwagi, koncentracji i funkcji wykonawczych. Wystąpienie zaburzeń kognitywnych może pogorszyć jakość życia i wpłynąć na decyzje dotyczące leczenia przeciwnowotworowego. W ostatnich latach zjawisko to wzbudza coraz więks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Yet the ECtHR maintains that restrictive prison regimes may be applied in a way which remains respectful of human dignity, insofar as they are orientated and tailored solely towards averting risks posed by the acts of the person subjected to them and with due safeguards for that person's health and well-being, 256 including their 'mental and physical stimulation' . 257 Following Vinter, the importance of rehabilitation is already playing and bound to continue to play a vital role in the Court's appraisal of the implications for human dignity of solitary confinement and other restrictive prison regimes. In Petukhov v Ukraine, for example, the ECtHR underlined States' 'positive obligation to secure prison regimes to life prisoners which are compatible with the aim of rehabilitation and enable such prisoners to make progress towards their rehabilitation' 258 and found that a regime whereby life prisoners are 'segregated from other prisoners and spend up to twenty-three hours per day in their cells … with little in terms of organised activities and association' was incompatible with the aim of rehabilitation and therefore with the requirement of reducibility under Article 3.…”
Section: The Court's Reasoning and The Puzzles Of Punishmentmentioning
confidence: 99%
“…Yet the ECtHR maintains that restrictive prison regimes may be applied in a way which remains respectful of human dignity, insofar as they are orientated and tailored solely towards averting risks posed by the acts of the person subjected to them and with due safeguards for that person's health and well-being, 256 including their 'mental and physical stimulation' . 257 Following Vinter, the importance of rehabilitation is already playing and bound to continue to play a vital role in the Court's appraisal of the implications for human dignity of solitary confinement and other restrictive prison regimes. In Petukhov v Ukraine, for example, the ECtHR underlined States' 'positive obligation to secure prison regimes to life prisoners which are compatible with the aim of rehabilitation and enable such prisoners to make progress towards their rehabilitation' 258 and found that a regime whereby life prisoners are 'segregated from other prisoners and spend up to twenty-three hours per day in their cells … with little in terms of organised activities and association' was incompatible with the aim of rehabilitation and therefore with the requirement of reducibility under Article 3.…”
Section: The Court's Reasoning and The Puzzles Of Punishmentmentioning
confidence: 99%